Treatment of Chemical and Biological Oxygen Demand on Batik-Modified Sasirangan Textile Wastwater Using Electrocoagulation Process - Paramita, Andika Putri; Mirwan, Agus; Mu'minah, Ridhayanti; Purnawilda, Agita; Irawan, Chairul - (Dinamika Kerajinan dan Batik: Majalah Ilmiah, 2023)
Electrocoagulation process on batik-modified sasirangan textiles wastewater treatment used aluminum electrodes (Al6061-T6) from the waste scraps of the aluminum furniture industry. Batch experiments at room temperature were carried out at an initial of pH 4. The parameters effect such as time reaction (5– 120 min), current density (3.5–5.5 mA/cm2), and the distance between the electrodes (2–5 cm) were evaluated to determine the optimum condition for COD and BOD5 removal. The optimum condition for the electrocoagulation process on batik-modified sasirangan textiles wastewater was selected at a time of 15 minutes, 5.5 mA/cm2 of current density, and 2 cm of electrode distances. Under those conditions around 59.60% of COD and 62.47% of BOD5 removal efficiencies were achieved. Both kinetics in COD and BOD5 removal with electrocoagulation reaction follows the half-order reaction. Reusing the leftover aluminum from furniture manufacturing as electrodes in the electrocoagulation process is quite effective for treated batik-modified sasirangan to meet the quality standard of clean water